Sears CEO Lampert's battle to turn Sears around - Eisen, Sara; Schatzker, Erik (Business and education in video, 2013)
Bloomberg Businessweek's Mina Kimes discusses Sears woes with Sara Eisen on Bloomberg Television's 'Market Makers.'